(untitled) (Journal of Student Affairs in Africa, 2023)
Graduate transitions and pathways do not naturally involve moving smoothly or sequentially from education into the world of work. Instead university graduates move through employment, entrepreneurship, unemployment and continued further education as they generate livelihoods. For African universities to be student-centred, with a focus on student development and success, the nature of these livelihood pathways must be examined in order to provide appropriate and relevant training and transition support. This article uses quantitative and qualitative data from African graduates who received a scholarship to complete their degrees at 21 universities (nine in Africa and 12 from other countries). Their post-graduation pathways are mapped and explored to determine how graduates generate livelihoods. The findings show that a minority of African graduates move smoothly from education into employment, and that for the majority, pathways are multidimensional and complex. While some move into the world of work with ease, most develop portfolios of income. By developing initiatives based on these findings, universities can help graduates navigate the challenges of income diversification, provide them with the necessary skills and resources, and foster a supportive ecosystem that encourages entrepreneurial thinking and diversified career paths.